The Resolution of Corruption Crimes with Connectivity Following the Constitutional Court Decision - Budi Pramono; Bambang Ariyanto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The resolution of corruption offenses related to connectivity, following the issuance of Constitutional Court Decision Number: 88/PUU-XXI/2023, requires careful scrutiny due to significant changes in case management mechanisms. Previously, the Corruption Eradication Commission (KPK) lacked jurisdiction over connectivity-related corruption cases; however, this ruling has granted it the authority to handle such matters. This research adopts a normative legal approach, utilizing both legislative and conceptual frameworks to examine the issue. Despite the ruling, the handling of connectivity-related offenses—including investigation, prosecution, and adjudication—remains misaligned with existing Indonesian legal frameworks. Currently, case management in this domain involves the Ministry of Defense, the Attorney General's Office, and the Headquarters of the Indonesian National Armed Forces through a permanent connectivity team. This team was established under the Joint Decision of the Minister of Defense Number: 2196/M/XII/2021, the Attorney General Number: 270 of 2021, and the Indonesian National Armed Forces Commander Number: Kep/1135/XII/2021, dated December 7, 2021. However, this decision does not yet integrate the Corruption Eradication Commission (KPK) or the National Police (Indonesian Police). As a result, if the KPK or the Police handle connectivity-related corruption cases, they must be processed separately (splitting), potentially leading to inconsistencies, inefficiencies, and accountability gaps in law enforcement. Such fragmentation could damage public trust in the justice system and negatively impact the reputation of the Indonesian National Armed Forces. If left unaddressed, these inefficiencies may lead to substantial financial losses for the state. The ruling introduces a shift in operational frameworks, emphasizing a collaborative decision-making process involving all relevant institutions, with careful consideration of military concerns.